ANALISIS PENGELOLAAN KEUANGAN BADAN USAHA MILIK DESA (BUMDes) DI DESA BAILANGU KECAMATAN SEKAYU KABUPATEN MUSI BANYUASIN - Irfansyah, Ahmad; Septariani, Jumania (Jurnal Ilmiah Akuntansi Rahmaniyah, 2024)
The objective of this study is to find out how the financial management of village-owned enterprises in BUMDes in Bailangu Village, Sekayu District, Musi Banyuasin Regency. The formulation of the problem in this study is how the financial management of Village-Owned Enterprises (BUMDes) in Bailangu Village, Sekayu District, Musi Banyuasin Regency. This study uses a qualitative method with data collection techniques, such as observation, interviews and documentation. The results of this study indicated that the financial management carried out in BUMDes in Bailangu Village, Sekayu District, Musi Banyuasin Regency is still guided by the Regulation of the Minister of Home Affairs Regulation 113 of 2014. Supervision by the village government by reviewing and examining reports sent by BUMDes to the Village Supervisory Agency (BPD) and experts who assisted BUMDes in running existing programs. The strategy carried out by BUMDes in Bailangu Village, Sekayu District, Musi Banyuasin Regency is to improve the quality of management and strengthen the organization, strengthen the management of BUMDes businesses and BUMDes business units which contain collaborative activities carried out by BUMDes with other existing entrepreneurs, BUMDes in Bailangu Village, Sekayu District, Musi Banyuasin Regency carries out promotions on social media.